Quantitative Analysis of the Cytoskeleton’s Role in Inward Rectifier KIR2.1 Forward and Backward Trafficking - Li, Encan; Loen, Vera; van Ham, Willem B.; Kool, Willy; van der Heyden, Marcel A. G.; Takanari, Hiroki (Frontiers in Physiology, 2022)
Alteration of the inward rectifier current IK1, carried by KIR2.1 channels, affects action potential duration, impacts resting membrane stability and associates with cardiac arrhythmias. Congenital and acquired KIR2.1 malfunction frequently associates with aberrant ion channel trafficking. Cellular processes underlying trafficking are intertwined with cytoskeletal function. The extent to which the cytoskeleton is involved in KIR2.1 trafficking processes is unknown. We aimed to quantify the dependence of KIR2.1 trafficking on cytoskeleton function. GFP or photoconvertible Dendra2 tagged KIR2.1 constructs were transfected in HEK293 or HeLa cells. Photoconversion of the Dendra2 probe at the plasma membrane and subsequent live imaging of trafficking processes was performed by confocal laser-scanning microscopy. Time constant of green fluorescent recovery (g,s) represented recruitment of new KIR2.1 at the plasma membrane. Red fluorescent decay (r,s) represented internalization of photoconverted KIR2.1. Patch clamp electrophysiology was used to quantify IKIR2.1. Biochemical methods were used for cytoskeleton isolation and detection of KIR2.1-cytoskeleton interactions. Cytochalasin B (20 μM), Nocodazole (30 μM) and Dyngo-4a (10 μM) were used to modify the cytoskeleton. Chloroquine (10 μM, 24 h) was used to impair KIR2.1 breakdown. Cytochalasin B and Nocodazole, inhibitors of actin and tubulin filament formation respectively, strongly inhibited the recovery of green fluorescence at the plasma membrane suggestive for inhibition of KIR2.1 forward trafficking (g,s 13±2 vs. 131±31* and 160±40* min, for control, Cytochalasin B and Nocodazole, respectively (*p<0.05 vs. control)). Dyngo-4a, an inhibitor of dynamin motor proteins, strongly slowed the rate of photoconverted channel internalization, whereas Nocodazole and Cytochalasin B had less effect (r,s 20±2 vs. 87±14*, 60±16 and 64±20 min (*p<0.05 vs. control)). Cytochalasin B treatment (20 M, 24 h) inhibited IKIR2.1. Chloroquine treatment (10 μM, 24 h) induced intracellular aggregation of KIR2.1 channels and enhanced interaction with the actin/intermediate filament system (103±90 fold; p<0.05 vs. control). Functional actin and tubulin cytoskeleton systems are essential for forward trafficking of KIR2.1 channels, whereas initial backward trafficking relies on a functional dynamin system. Chronic disturbance of the actin system inhibits KIR2.1 currents. Internalized KIR2.1 channels become recruited to the cytoskeleton, presumably in lysosomes.